2020
DOI: 10.1111/pai.13230
|View full text |Cite
|
Sign up to set email alerts
|

Adverse pregnancy outcomes and risk of later allergic rhinitis—Nationwide Swedish cohort study

Abstract: Background: Perinatal conditions may be associated with future allergic disease; however, data are conflicting and incomplete for childhood allergic rhinitis (AR). The aim of this study was to examine pregnancy outcome (cesarean delivery, preterm birth, low birthweight) and offspring AR as defined by national registers.Methods: Nationwide longitudinal cohort study using prospectively recorded register data from 1 059 600 singleton livebirths born in Sweden in 2001-2012. Cox regression adjusted for infant sex a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 41 publications
5
20
0
1
Order By: Relevance
“…The present paper showed that a negligible association exists be- Our results (asthma was not reported here as an outcome) are in line with previous studies with a longer-than-five-year follow-up and meta-analyses, which have reported the association between CS or assisted VD and allergic rhinitis or asthma. 7,8,[10][11][12][13]19 Insufficient or no associations between the delivery mode and atopic diseases have been reported in studies with a shorter follow-up 16,17 but also in two cohorts with 12 years of follow-up. 18 According to a recent finding, the association between CS and asthma was modified by sex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present paper showed that a negligible association exists be- Our results (asthma was not reported here as an outcome) are in line with previous studies with a longer-than-five-year follow-up and meta-analyses, which have reported the association between CS or assisted VD and allergic rhinitis or asthma. 7,8,[10][11][12][13]19 Insufficient or no associations between the delivery mode and atopic diseases have been reported in studies with a shorter follow-up 16,17 but also in two cohorts with 12 years of follow-up. 18 According to a recent finding, the association between CS and asthma was modified by sex.…”
Section: Discussionmentioning
confidence: 99%
“…5 Thus far, findings are conflicting on the relationship between delivery mode and atopy 6 ; both positive and no (or insufficient) associations have been reported. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] The associations have been suggested to be confounded, or the effect modified by other risk factors was related to the delivery mode or microbiota composition such as duration of breastfeeding, birth order, sex, maternal atopy or early pet exposure. 12,15,[20][21][22] A short follow-up period may also explain the insufficient or conflicting findings.…”
Section: Introductionmentioning
confidence: 99%
“…13 Our results are consistent with previous research, 9,10,12,17,22,29 however, some studies contradict our conclusions or show no association. 15,21,30,31 Our study makes a significant addition to the literature due to its longitudinal design including repeated measurements of outcome throughout childhood up to early adulthood. Additionally, our results were replicated in an independent data set.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that babies born by cesarean section might have a modified microbiota, and this can influence the number of obstructive lung diseases in young children, 6 similar to the use of antibiotics during pregnancy or early life, which also modifies the microbiota 7 . Overall, the factors associated with pregnancy or early‐life events of the development of bronchiolitis and asthma have been frequently studied recently 8‐11 (Figure 1).
…”
mentioning
confidence: 99%